Surface Morphology And Formation Of Nanostructured Porous GaN By UV-Assisted Electrochemical Etching. - L, S Chuah; Hassan, Z.; C, W Chin; Abu Hassan, H (2009)
This article reports on the studies of porous GaN .prepared by ultra-violet (UV) assisted electrochemical etching in a solution of 4:1:1 HF: CH30H:H202 under illumination of an UV lamp with 500 W power for 10, 25 and 35 minutes.